Panel Data Analysis of External Debt Drivers in Lower-Middle and Upper-Middle Income Countries - Beenish, Humaira; Rashad, Muhammad; Siddiqui, Sidra; Sabir, Nadia; Khan, Asif (iRASD Journal of Economics, 2024)
In order to investigate the macroeconomic factors contributing to foreign debt in Lower Middle-Class and Upper Middle-Class countries, this study adopts a panel data approach that covers the years 2005–2020 for 16 countries in each income group. Using fixed and random effect techniques, the study determines significant variables that affect foreign debt. It is interesting to observe that foreign direct investment influences negatively on foreign debt in lower-middle-income countries but a positive significant impact in upper-middle income group economies. Moreover, the effect of exports is inverse and substantial on foreign debt in the lower-middle income group; in the upper-middle income group, the impact is negligible and positive. At the end, the impact of government spending is not meaningful on foreign debt in both income groups. Based on the findings, this research pinpoints the essential of policy formulation on the behalf of income classifications and also highlights the considerations to identify a variety of economic circumstances when investigating the factors influencing foreign debt.